Nilai-Nilai Kepemimpinan Islam dalam Buku Islamic Golden Stories Karya Ahmad Rofi’ Usmani - Atika Muliyandari; Nurul Arafah (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2023)
In this era of increasingly advanced development, many people forget and abandon the true meaning of leadership. This study aimed to discover Islamic leadership's values in the book Islamic Golden Stories by Ahmad Rofi' Usmani. The type of research used is library research, then uses a qualitative approach with an inductive thinking method. After the analysis phases were carried out, it was found that there was compatibility between the values ​​of Islamic leadership and the book Islamic Golden Stories by Ahmad Rofi' Usmani. These Islamic leadership values ​​include Siddiq, namely daring to admit mistakes and being responsible, amanah, namely being trustworthy; exemplary; be fair; high lead loyalty; and loving the people, tabligh consists of listening to advice and carrying out tasks, and fatonah consists of broad-mindedness; wise; able to control emotions; and have innovation. Then, the values ​​of Islamic leadership have contributed to the leadership of school principals because the values ​​of Islamic leadership in the book Islamic Golden Stories by Ahmad Rofi' Usmani are in conformity with the Regulation of the Minister of Education Number 13 of 2007 concerning school principal leadership which includes personality competence, competence managerial, entrepreneurial competence, supervision competence, and social competence.